The never-ending revival : Rounder Records and the Folk Alliance - Scully, Michael F. (Music in American life., 2008)
"In the late 1950s through the 1960s, the folk music revival pervaded the mainstream music industry, with artists such as Bob Dylan and Joan Baez singing historically or politically informed ballads based on musical forms from Appalachia and the South. In the twenty-first century, the revival continues, and it includes a variety of music derived from Cajun, African American, and Mexican traditions, among many others. Even though the mainstream music industry and media largely ignore the term "folk music," a strong allure based on nostalgia, the desire for community, and a sense of exclusiveness augments an enthusiastic following connected by word-of-mouth, numerous festivals, and the Internet. There are more folk festivals now than there were during the original boom of the 1960s, suggesting that music artists, agents, and record label representatives are striking a successful balance between tradition and profitability. Scully combines rich interviews of music executives and practicing folk musicians with valuable personal experience to reveal how this American subculture remains in a "never-ending revival" based on fluid definitions of folk and folk music."--Jacket.